Exploring the Techniques Used by the Machine and Human Translation in Translating The Gift of the Magi into Indonesian - Sujiyani, Erma; Syeba, Sulamit; Norahmi , Maida; Riniyati, Riniyati (General English Education, 2025)
The pros and cons of which one is better in producing good result of translation between Machine Translation (MT) and Human Translation (HT) has been going on for many years. In the attempt to observe which is better between MT and HT, this article focuses on exploring the techniques used by U-Dictionary as a MT and Maggie Tiojakin as a HT in translating The Gift of the Magi into Indonesian. Data in this research are the words, phrases, clauses and sentences related to the translation techniques in the original version of The Gift of the Magi and the two translation versions. The collected data are analyzed qualitatively by using Molina and Albir’s (2002) theory. The results describe that Maggie Tiojakin used 12 techniques; they are adaptation, amplification, compensation, description, discursive creation, established equivalent, generalization, literal translation, modulation, particularization, reduction, and transposition. Meanwhile, U-Dictionary used 8 techniques; they are amplification, borrowing, calque, established equivalent, literal translation, modulation, reduction, and transposition. The dominant translation technique used by Maggie Tiojakin is discursive creation (24.54%), whereas in U-Dictionary, it is literal translation (47.27%). From the different translation techniques used, it can be proven that HT uses more various techniques and has better translation result than MT, in which the translation of the literary works especially a short story done by HT is more accurate, readable, and acceptable.